A Study on Social and Political Implications of Internet Based Communities in India: Understanding the Impact of Internet-based Communities on Politics in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In recent years, social media are said to have an impact on the public discourse and communication in the society. In particular, social media are increasingly used in political context. More recently, micro blogging services (e.g., twitter) and social network sites (e.g., Facebook) are believed to have the potential for increasing political participation. While Twitter is an ideal platform for users to spread not only information in general but also political opinions publicly through their networks, political institutions (e.g., politicians, political parties, political foundations, etc.) have also begun to use Face book pages or groups for the purpose of entering into direct dialogs with citizens and encouraging more political discussions. Previous studies have shown that from the perspective of political institutions, there is an emerging need to continuously collect, monitor, analyze, summarize, and visualize politically relevant information from social media. These activities, which are subsumed under “social media analytics,” are considered difficult tasks due to a large numbers of different social media platforms as well as the large amount and complexity of information and data. Systematic tracking and analysis approaches along with appropriate scientific methods and techniques in political domain are still lacking. In this paper, we propose a methodological framework for social media analytics in political context and for this we have taken 230 respondents. More specifically, our framework summarizes most important social media perspective of political implications.